Relative Wealth Concerns and Financial Bubbles - DeMarzo, Peter M.; Kaniel, Ron; Kremer, Ilan (Review of Financial Studies, 2008)
[We present a rational general equilibrium model that highlights the fact that relative wealth concerns can play a role in explaining financial bubbles. We consider a finite-horizon overlapping generations model in which agents care only about their consumption. Though the horizon is finite, competition over future investment opportunities makes agents' utilities dependent on the wealth of their cohort and induces relative wealth concerns. Agents herd into risky securities and drive down their expected return. Even though the bubble is likely to burst and lead to a substantial loss, agents' relative wealth concerns make them afraid to trade against the crowd.]